(untitled) (Journal of the College of Basic Education, 2022)
Effect of zinc ion concentration of ZnO thin films, prepared by using chemical bath deposition technique, is discussed. ZnO films were characterized using different techniques such as X-ray diffraction (XRD), electrical resistivity measurement, and optical absorption and transmission. The XRD analysisshowed that all the films had a preferred (002) orientation. The ZnO films showed, on average 20% reflectance, the transmittance range between 35% and 45% for different morality before annealing. Optical band gap decreases with increasing zinc ion concentration. Linear increase in resistivity with increasingin molarities was shown. The films were annealed at 473 K and showed decreases in the reflectance of the films, but transmitting increase to 75% - 80%. Therefore by annealing process the hydroxide phase converted to the oxide phase. The annealed samples show a relative decrease in band gap with annealing.